Expropriação do Fundo Nacional de Assistência Social em favor do capital: consequências do (des)financiamento em Aracaju/SE - Ferreira, Cristiane de Oliveira (2024)
The present dissertation aims to analyze, in a general sense, how the treasury of the municipality of Aracaju has been burdened and its consequences through the ongoing financing of social assistance. Throughout the research investigations, we sought to examine the consequences in light of the defunding by the Federal Government and the underfunding by the State Government of Sergipe during the period from 2016 to 2022. Among other objectives, we emphasize: analyzing the budgetary aspects of the Municipal Social Assistance Fund of Aracaju/SE within a temporal framework that delimits the administrations of Michel Temer and Jair Bolsonaro; investigating the volume of resources invested in the Unified Social Assistance System (SUAS) in Aracaju from different funding sources; identifying whether there was an increase in municipal resources during the period for the maintenance and/or expansion of services, programs, projects, and benefits of SUAS in Aracaju/SE. The theoretical methodological approach adopted was the historical- dialectical materialism, whose transient socio-historical mediations are apprehended in light of the totality of social life in its essence (Kosik, 2002). This is a documentary and bibliographical research, which we conducted based on quanti-qualitative information and data extracted from consultations in primary and secondary sources available on official websites, reports, and references, carefully selected concerning the theme/object. In light of the reflections based on the cited literature, we can indicate some analytical devices: the intensification of the ultraneoliberal State policy through setbacks in the field of social security, increasingly subsumed to the salvationist interests of the accumulation crises of financial oligarchic groups, in the face of the scenario of increasing unemployment, poverty, and hunger exacerbated from 2020, the context of the Covid-19 pandemic. Such structural and conjunctural elements bring implications to the emptying of spaces for debates and struggles in defense of social rights, which have been constrained in the new phase of financial capitalism, the "Interest-Bearing Capital." The maintenance of the economic policy anchored in the tripod: inflation targets, primary surplus, and floating exchange rate adopted since the government of Fernando Henrique Cardoso (FHC) is responsible for the constant difficulties in developing infrastructure policies, mainly the social security policy. It is worth noting that in the current conjuncture of Brazil, intense disputes are observed with globalized financial capital, which has been seizing part of the resources from public funds while channeling them to pay off public debt interest, in addition to accessing previously forbidden resources. The data obtained from this research demonstrate that both the union and the State of Sergipe and the municipality of Aracaju have historically, between the years 2016 to 2022, invested more resources in paying off public debt charges than in offering social assistance programs, projects, services, and benefits. Furthermore, we found that in Aracaju, during the period, the municipality financed an average of 83% of SUAS actions, compared to the average of 14.54% from the Union and 1.29% from the state. There was an increase in investments in the area with the municipality's own resources, but even so, the portion of the budget execution being used for the payment of interest and debt charges is greater than that invested in social assistance and is increasing, resulting in limitations of services for families in need, even in the face of the worsening and reconfiguration of expressions of the social issue, deepening social inequalities.